2009
DOI: 10.1089/jmf.2008.1185
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Dietary Red Ginseng on Epidermal Hydration and Ceramide Levels in Ultraviolet-Irradiated Hairless Mice

Abstract: Ultraviolet (UV) irradiation induces skin dryness, largely by disruption of the epidermal barrier. In a search for dietary and plant compounds that would protect against skin dryness, we investigated the dietary effect of red ginseng (the steamed root of Panax ginseng C.A. Meyer) on epidermal levels of hydration and ceramides, the most important lipids for maintaining the epidermal barrier, in UV-irradiated mice. Albino hairless mice were fed either control diets (group UV [UV-irradiated control]) or diets wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…In chronic UV-irradiated skin of hairless rat, decreased ceramide levels were observed and attributed to abnormal sphingomyelinase [25]. It is also reported that high ceramidase expression causes a decrease in ceramide levels in the epidermis [17]. These findings were consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In chronic UV-irradiated skin of hairless rat, decreased ceramide levels were observed and attributed to abnormal sphingomyelinase [25]. It is also reported that high ceramidase expression causes a decrease in ceramide levels in the epidermis [17]. These findings were consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The mRNA expression level does not represent the production amount of specific proteins from mRNA. However, reported studies showed that the mRNA expression level of SPT and ceramidase correlated consistently with their protein level [19,27]. Thus, we investigated SPT and ceramidase mRNA expression in hairless mice.…”
Section: Discussionmentioning
confidence: 93%
“…Various beneficial pharmacological effects of ginseng or its components have been reported, including anti-cancer, anti-allergy, anti-inflammatory, anti-fatigue, anti-stress, and immunomodulatory activities (Kim et al, 2002; Park et al, 2004; Sumiyoshi et al, 2010; Lee and Cho, 2011). Red ginseng is produced by steaming fresh ginseng at 95°C to 100°C for a reasonable time (Kim et al, 2009). It is known to have greater pharmaceutical efficacy and functionality than white ginseng, due to its high saponin content (Kim and In, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These results are important because filaggrin in stratum corneum are incorporated into lipid envelopes and release free amino acids to assist in water retention [26], [24], [25]. Another previous study reported that dietary supplementation of red ginseng protected skin from UV-induced dryness with an accumulation of ceramides via elevated expression of serine palmitoyltransferase, a key enzyme involved in de novo ceramide synthesis [27]. With all these previous results, we could suggest that BG11001 improved human eye wrinkle roughness by the regulation of collagen type I expression, and BG11001 was also able to increase skin elasticity and maintain moisture content by inhibition of filaggrin expression and elevation of serine palmitoyltransferase expression.…”
Section: Discussionmentioning
confidence: 99%